2017
DOI: 10.1371/journal.pone.0177533
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone marrow mesenchymal stromal cell derivatives in skin wound healing in diabetic mice

Abstract: Mesenchymal stromal cells (MSCs) have shown to be a promising tool in cell therapies to treat different conditions. Several pre-clinical and clinical studies have proved that the transplantation of MSCs improves wound healing. Here, we compare the beneficial effects of mouse bone marrow-derived allogeneic MSCs (allo-mBM-MSCs) and their acelullar derivatives (allo-acd-mMSCs) on skin wound healing in Non-Obese Diabetic (NOD) mice. One dose of allo-mBM-MSCs (1×106 cells) or one dose of allo-acd-mMSCs (1X) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 63 publications
2
66
0
1
Order By: Relevance
“…A total of 5 × 10 5 rat BM‐MSCs were seeded onto six‐well plates and cultured in respective condition medium. Alkaline phosphatase staining and Oil Red O staining were performed to confirm osteogenesis and adipogenesis, respectively …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 5 × 10 5 rat BM‐MSCs were seeded onto six‐well plates and cultured in respective condition medium. Alkaline phosphatase staining and Oil Red O staining were performed to confirm osteogenesis and adipogenesis, respectively …”
Section: Methodsmentioning
confidence: 99%
“…Optimum healing of a cutaneous wound requires a well‐orchestrated integration of complex biological and molecular events of cell migration and proliferation and includes extracellular matrix deposition and remodelling. Several studies in recent years have suggested that bone marrow‐derived stem cells such as mesenchymal stem cells (MSCs), progenitor cells such as endothelial progenitor cells and fibrocytes, may be involved in these processes, contributing to skin cells or releasing regulatory cytokines . Stem/progenitor cells may be mobilized to leave the bone marrow, migrate to injured tissues and participate in repair and regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Among the cytokines and growth factors, the interleukin-6 (IL-6) has a participation in the initiation and maintenance of the inflammatory reaction 4,5,[23][24][25] . Other chemokine involved in the inflammatory reaction is the vascular endothelial growth factor (VEGF), an angiogenic factor that increases the vascular permeability 26 favouring the recruitment of inflammatory cells in the beginning of the inflammatory reaction 27 , and plays an essential role in the tissue remodelling 28 and wound healing 27 .…”
mentioning
confidence: 99%
“…Bone marrow MSCs have been known to differentiate into a wide variety of mesenchymal cell types, including bone, cartilage and fat cells [9-11] and even into cells beyond its originating phenotype, such as cardiomyocytes and neurons [12,13]. In applications to the skin, bone marrow aspirate, bone marrow mononuclear cells, and a combination of cells and biomaterial have been used [14][15][16][17]. In a study utilizing autologous bone marrow aspirate [14], 75 patients with chronic wounds were enrolled.…”
Section: Bone Marrow Mscsmentioning
confidence: 99%
“…Bone marrow MSCs have been explored as a treatment option [15][16][17]. In one study, allogeneic MSCs were compared to the MSCs' acellular derivatives in a non-obese diabetic (NOD) mouse model [15].…”
Section: Bone Marrow Mscsmentioning
confidence: 99%